Bioethics in a transformation society on the example of the legal regulation - M.M. Blikhar; I.M. Zharovska; N.V. Ortynska; I.I. Komarnytska; R.M. Matkivska (Репродуктивная эндокринология, 2023)
The article is devoted to bioethical problems that exist in a transformational society. The most important issues are considered, including organ and tissue transplantation, use of embryonic and stem cells for the treatment, gene therapy, in vitro fertilization, cloning, etc. It is emphasized that along with scientific progress there are deep transformations connected with this process in the socio-psychological and cultural spheres, the reason for which is the penetration into mass culture and the mentality of new ideas, conceptions and terms. Emphasis was placed on the need to create a DNA database of servicemen, which is especially relevant during the wartime in Ukraine. Attention is drawn to the need to create special legislation for quality legal regulation of surrogacy, which is especially relevant today. The problems of biomedical transformations and their conflict became the subject of consideration by scientists. Recent studies are devoted to a number of issues related to updating the understanding of the determinants of bioethics in various directions. First of all, attention should be paid to the genesis of the basic standards of bioethics. T. Beauchamp and J. Childress in many editions and reprints have transformed the understanding of the problem over forty years, and it is now agreed that it should be considered within four broad moral principles: respect for autonomy, benevolence, and justice. They can and should be seen as arising historically and philosophically from general morality, as universal morality (as opposed to pure relativism or pluralism) gradually became an integral part of the principled approach. Taking into account all the latest trends in the field of biomedicine, the purpose of this article is to address the problem of the development of biomedical legal standards in Ukraine and the issues of combining them with national identity in the current conditions of the pandemic crisis. The relevance of this topic is important for several reasons: it can serve as a basis for a comparative analysis of the practical application of biomedical legal standards; the example of Ukraine is valuable as an experimental benchmark of the legal policy of the states of the former USSR for the analysis of the development of the post-Soviet socio-legal and cultural sphere; will make it possible to interpret identity in the context of globalized changes.